Relationship between thermal comfort and driving performance among Malaysian bus driver - Ahmad Rasdan, Ismail; Siti Nur Atikah, Abdullah; Ahmad Adam, Abdullah; Ab Hamid, Mohd Rashid; Baba, M. Deros (Asian Research Publishing Network (ARPN), 2015)
The purpose for this paper is to investigate the correlation between thermal comfort and Malaysian bus driver’s performance and also to determine the response from bus drivers regarding the prevalence discomfort that they experience along their journey. In this study, descriptive or survey study was used. A questionnaire survey was conducted to examine the relationship between thermal comfort and environmental factors that influences the Malaysian bus drivers’ performance. In this study, focus are been given to Kuantan bus drivers with sample size approximately 260 drivers. The confidence level is 95% and degree of accuracy of 0.05. From this population, the sample was selected randomly. The descriptive analysis and correlation was used to analysis the raw data that get from feedback of survey. The ‘p’ value is less than the alpha value, and then there is evidence that the relationship is significant. Therefore, null hypothesis is rejected. Hence, it proved that there is statistically significant positive correlation between thermal comfort and Malaysian bus driver performance. Clearly that all of two parts of thermal comfort and environmental factors have significantly correlated on Malaysian bus driver performance.